Presentation - Tolias, George (The Historical Review/La Revue Historique, 2023)
This Special Section is dedicated to the Digital Atlas of the Greek War of Independence and the Creation of the Greek State (1821–1852), a digital mapping project conducted by the Institute of Historical Research / National Hellenic Research Foundation and generously funded by the Hellenic Foundation for Research and Innovation. The atlas is based on the historical maps and their related source materials produced during the period under study, and firsthand testimonies of the Greek War of Independence extracted from memoirs of combatants. It proposes a digital reconstruction of the historical landscape of Greece during the crucial years of the emergence of the Greek state and offers a research tool for information on the Greek space and the revolutionary events.